Reliability of Interleukin-6 Alone and in Combination for Diagnosis of Early Onset Neonatal Sepsis: Systematic Review - Eichberger, Julia; Resch, Bernhard (Frontiers in Pediatrics, 2022)
Neonatal sepsis is a major cause of morbidity and mortality in both preterm and term infants. Early-onset neonatal sepsis (EONS) presents within the first 72 h of life. Diagnosis is difficult as signs and symptoms are non-specific, and inflammatory markers are widely used to confirm or rule out neonatal sepsis. Interleukin-6 (IL-6) is part of the fetal inflammatory response syndrome (FIRS) and therefore an interesting early marker for neonatal sepsis. The main objective for this review was to assess the diagnostic potential of IL-6, alone and in combination, for diagnosis of early neonatal sepsis (EONS) in term and preterm infants, in cord and peripheral blood, and in dependence of timing of sample collection. IL-6 diagnostic accuracy studies for diagnosing EONS published between 1990 and 2020 were retrieved using the PubMed database. We included 31 out of 204 articles evaluating the potential of IL-6 for the diagnosis of EONS in a study population of newborns with culture-proven and/or clinically suspected sepsis. We excluded articles dealing with neonatal bacterial infections other than sepsis and biomarkers other than inflammatory markers, those written in languages other than English or German, studies that did not distinguish between EONS and late-onset sepsis, and animal and in vitro studies. Full-text articles were checked for other relevant studies according to the PRISMA criteria. We identified 31 studies on IL-6 diagnostic accuracy for EONS diagnosis between 1990 and 2020 including a total of 3,276 infants. Sensitivity and specificity were reported, and subgroup analysis was performed. A STARD checklist adapted for neonates with neonatal sepsis was used for quality assessment. The range of IL-6 sensitivity and specificity in neonatal samples was 42.1–100% and 43–100%; the median values were 83 and 83.3%, respectively. IL-6 accuracy was better in preterm infants than in mixed-study populations. Early sample collection at the time of sepsis suspicion had the highest sensitivity when compared to other time points. Cord blood IL-6 had higher diagnostic value compared to peripheral blood. The biomarker combination of IL-6 and CRP was found to be highly sensitive, but poorly specific. Limitations of this review include use of only one database and inclusion of a heterogeneous group of studies and a small number of studies looking at biomarker combinations; a strength of this review is its focus on early-onset sepsis, since type of sepsis was identified as a significant source of heterogeneity in IL-6 diagnostic accuracy studies. We concluded that IL-6 has a good performance as an early diagnostic marker of EONS within a study population of preterm infants, with best results for cord blood IL-6 using cutoff values above 30 pg/ml.